LDP alleviates TKI-induced proteinuria through reversing the expression of RelA in renal tissues - Fu, Zhou; Zhang, Su; Gu, Xiaoying; Guan, Tao; Wang, Chengmeng; Zhang, Jiaqi; Wang, Yun; Guo, Hua; Wang, Lu; Zhang, Ti (Frontiers in Medicine, 2023)
Tyrosine kinase inhibitors (TKIs), as an important tumor therapy, can induce severe proteinuria that significantly affects anti-tumor therapy. Existing therapies against proteinuria induced by other etiologies are currently ineffective for TKI-induced proteinuria. It has been shown that various types of proteinuria are related to podocyte damage caused by changes in the RelA signaling pathway. Our experiments confirmed that TKIs activate the renal RelA signaling pathway, and induce death of podocytes and destruction of the glomerular filtration barrier. Here we found that Liuwei Dihuang Pill (LDP) attenuated the inflammatory injury of podocytes through inhibiting activation of RelA, and subsequently relieved TKI-related proteinuria and prevented the progression of TMA and FSGS. Our finding indicated that LDP may be effective for the treatment of TKI-induced proteinuria, which is clinically significant.